Glycerolysis-intertesterification of Palm Stearin and Nyamplung Oil Mixture in High Shear Continuous Stirred Tank Reactor - Bonifasius Rionaldo; Rini Yanti; Chusnul Hidayat (agriTECH, 2023)
Glycerolysis-interesterification can be used for the synthesis of products containing high total Mono- and Diacylglycerol (MDAG). Therefore, this study aimed to evaluate the synthesis of products rich in MDAG content using glycerolysis-interesterification method in High Shear Continuous Stirred Tank Reactor (HS-CSTR). The impact of varying material flow rates (6, 10, 14, 18, and 22 mL/min) and processing time on the concentration of MDAG, physical properties of the resulting product, and consistency of product quality throughout the process were assessed. Furthermore, glycerolysis-interesterification reaction was performed at a temperature of 120 °C, with a glycerol and oil mixture mole ratio of 1:5 (mol/mol), 3% NaOH, and a stirring speed of 2000 rpm. Oil mixture consisted of Palm Stearin (PS) and Nyamplung oil (Calophyllum inophyllum) (MC) with a PS:MC mole ratio of 80:20 (mol/mol). Subsequently, the acylglycerol concentration and physical properties of the product were analyzed. The results showed that the material flow rate had a significant effect on MDAG and the physical properties of the product. The highest MDAG was obtained at a flow rate of 6 mL/min with content of 58.56±0.91%, and Slip Melting Point (SMP) of 41.44±0.08 °C and 42.9±0.03 °C. The hardness, emulsion capacity, and stability values were 10.88±0.22 N, 85.2±6.93%, and 88.7±5.00%, respectively. The acylglycerol concentration and physical properties of the product did not significantly fluctuate throughout the process, indicating that the process had achieved a steady state condition.